Brain abscess: A rare complication in a child with tetralogy of Fallot. (2020) - Lakhani, Murk; Memon, Roha Saeed; Khan, Fahad
Abstract: Brain abscess is a rarely occurring fatal complication accounting for 5%–18.7% of the population with cyanotic congenital heart diseases. Cyanotic heart diseases are associated with a right-to-left shunt that bypasses pulmonary circulation and results in tissue hypoxia and cyanosis. The most common cyanotic congenital anomaly seen is the tetralogy of Fallot. Herein, we discuss a case of uncorrected tetralogy of Fallot presenting as a parieto-occipital abscess in a 13-year-old boy. The patient was managed conservatively on intravenous antibiotics due to the small size of the abscess and then referred to cardiothoracic surgeons for the repair of the defect. The purpose of reporting this case is to highlight the importance of early detection and correction of cardiac defects to prevent serious complications resulting in childhood morbidity and mortality.